2018
DOI: 10.3389/fchem.2018.00156
|View full text |Cite
|
Sign up to set email alerts
|

Compressible and Recyclable Monolithic g-C3N4/Melamine Sponge: A Facile Ultrasonic-Coating Approach and Enhanced Visible-Light Photocatalytic Activity

Abstract: Powdery photocatalysts seriously restrict their practical application due to the difficult recycle and low photocatalytic activity. In this work, a monolithic g-C3N4/melamine sponge (g-C3N4/MS) was successfully fabricated by a cost-effective ultrasonic-coating route, which is easy to achieve the uniform dispersion and firm loading of g-C3N4 on MS skeleton. The monolithic g-C3N4/MS entirely inherits the porous structure of MS and results in a larger specific surface area (SSA) than its powdery counterpart. Bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…42 The other smaller peak around 13.1 could be indexed to (100) plane which corresponds to in-planar structural packing motif. [43][44][45] The (100) peak was found to be intense and narrow for g-C 3 N 4 samples at 550 to 650 C, indicative of higher degree of polymerisation. The broader peak for samples at 450 and 500 C is indicative of low degree of polymerization of g-C 3 N 4 .…”
Section: Xrd Analysismentioning
confidence: 97%
“…42 The other smaller peak around 13.1 could be indexed to (100) plane which corresponds to in-planar structural packing motif. [43][44][45] The (100) peak was found to be intense and narrow for g-C 3 N 4 samples at 550 to 650 C, indicative of higher degree of polymerisation. The broader peak for samples at 450 and 500 C is indicative of low degree of polymerization of g-C 3 N 4 .…”
Section: Xrd Analysismentioning
confidence: 97%
“…This novel photoactive composite has shown decent photooxidation ability according to NO photoremoval experiment (optimum activity = 78.6%) besides effective CO 2 photoreduction in comparison to powder g-C 3 N 4 . 118 This is a post-embedding technique yet the potential leaching of g-CN particles should be investigated in detail.…”
Section: ■ Sponges/foamsmentioning
confidence: 99%
“…Li et al [64] reported a C 3 N 4 supported Pd nanoparticles catalyst (PdCN) for photocatalytic oxidation of NO x ; this PdCN was found to have a better purification effect on NO in the air, reaching a maximum of 51.5% in the first 5 min, followed by stabilization at 44.9%. Yang et al [71] successfully synthesized a g-C 3 N 4 /melamine sponge (g-C 3 N 4 /MS) using the ultrasonic coating method with g-C 3 N 4 uniform dispersion and immobilization on the melamine skeleton (Fig. 8a-d).…”
Section: Graphite-phase Carbon Nitride and Its Complexmentioning
confidence: 99%